Lewis Base Catalysis Enables the Activation of Alcohols by means of Chloroformates as Phosgene Substitutes. Issue 22 (16th September 2020) - Zoller, Ben; Stach, Tanja; Huy, Peter H.
Abstract: Nucleophilic substitutions (S N ) are typically promoted by acid chlorides as sacrificial reagents to improve the thermodynamic driving force and lower kinetic barriers. However, the cheapest acid chloride phosgene (COCl2 ) is a highly toxic gas. Against this background, phenyl chloroformate (PCF) was discovered as inherently safer phosgene substitute for the S N ‐type formation of C−Cl and C−Br bonds using alcohols. Thereby, application of the Lewis bases 1‐formylpyrroldine (FPyr) and diethylcyclopropenone (DEC) as catalysts turned out to be pivotal to shift the chemoselectivity in favor of halo alkane generation. Primary, secondary and tertiary, benzylic, allylic and aliphatic alcohols are appropriate starting materials. A variety of functional groups are tolerated, which includes even acid labile moieties such as tert ‐butyl esters and acetals. Since the by‐product phenol can be isolated, a recycling to PCF with inexpensive phosgene would be feasible on a technical scale. Eventually, a thorough competitive study demonstrated that PCF is indeed superior to phosgene and other substitutes. Abstract : As substitute for hazardous and gaseous phosgene, phenyl chloroformate enables the activation of alcohols to halo alkanes in the presence of an appropriate Lewis base catalyst. Indeed, 1‐formylpyrrolidine (FPyr) or diethylcyclopropenone (DEC) are crucial as catalytic species to drive the chemoselectivity from phenyl carbonate to the desired alkyl halide formation. The isolation of the by‐product phenol shows that conceptually a recycling by means of inexpensive phosgene is feasible.